REKONSTRUKSI PENDIDIKAN SURAU DI MINANGKABAU (TINJAUAN ANALISIS PSIKOLOGI SOSIAL) - Afrinaldi Afrinaldi (Ta'dib, 2009)
This paper aims at portraying the educational process in surau in the past and explaining basic differences the process at present time. This study tries to reveal the urgency of reviving the main role of surau as the center of knowledge development and shifting the present traditional paradigm of surau from the place for worshiping, reciting Holy Quran, and Islamic teaching toward the center for data and information which in turn the center for knowledge development. Historically, the role of surau in the past was successful to produce qualified spiritual role figures. In contrast, surau, as the asset of nagari at present time, seemingly does not interest young generation. This article therefore tries to present some innovative ideas in reviving and developing educational system in surau through sociopsychological approach.  Kata kunci: analisis, pendidikan surau, psikologi sosial